Систематика зеленых жаб (Amphibia, Anura) фауны СССР - Писанец, Е.М.; Щербак, Н.Н. (Вестник зоологии, 1979)
Caryological and morphological analysis of green toads of the USSR fauna showed the presence of the polyploid (Bufo danatensis Pisanetz, 1978) and diploid (B. viridis Laur, 1768) species. The former is distributed in Southern Turkmenistan, Uzbekistan, Tajikistan, Kirghizia as well as in south-eastern Iran, Afghanistan and north-western India; it consists of two forms — submountain B. danatensis danafensis and alpine B. danatensis pseudoraddei. The diploid species is also heterogeneous: in the European part of the USSR and in the Caucasus the nominative subspecies is distributed, in the plain Middle Asia — B. viridis turanensis and in the south and south-east in the mountain Middle Asia — the subspecies B. v. asimonlanus ssp. n. A key of the B. viridis subspecies is presented.